(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper examines the distribution range of perennial herbaceous plants of the genus Aconitum. Particular attention is paid to the chemical composition, particularly the alkaloid aconitine, which is responsible for the plant’s high toxicity. The role of Aconitum in pharmacology and its uses are described.